Let‐7e as Potential Diagnostic Biomarkers in Early Detection of Peri‐Implant Diseases: A Cross‐Sectional Study - Nurul Latifah Zainal Abidin; Norjehan Latib; Fouad Hussain Al‐Bayaty; Mohd Faizal Hafez Hidayat (Clinical and Experimental Dental Research, 2025)
ABSTRACT Objectives Peri‐implant diseases (PID), specifically peri‐implant mucositis and peri‐implantitis, significantly jeopardize dental implant success. Traditional diagnostic methods, relying on periodontal probing and radiographs, have limitations in precisely diagnosing these conditions. Recent studies suggest that microRNA (miRNA) profiling might be a breakthrough in the early detection of PID. This study aimed to evaluate the expression levels of specific miRNAs—miR‐98, miR‐145, miR‐146a, and let‐7e—in individuals with peri‐implant mucositis and peri‐implantitis compared to a healthy control. Methods From January 2022 to October 2023, 19 participants with 38 dental implants were recruited according to established criteria. After clinical and radiographic evaluations, dental implants were grouped as peri‐implant health (Group 1), peri‐implant mucositis (Group 2), and peri‐implantitis (Group 3). Subsequently, peri‐implant crevicular fluid (PICF) samples were collected and analyzed through real‐time quantitative polymerase chain reaction (qPCR). Results Based on the findings, only let‐7e biomarkers were consistently detected across all samples, with their expression increased eightfold in peri‐implant mucositis and 94‐fold in peri‐implantitis cases. Kruskal–Wallis's test showed a statistically significant difference in relative gene expression of let‐7e between the different groups, H(2) = 25.825, p ≤ 0.001. Conclusions Our study indicates that miRNA biomarkers, particularly let‐7e, may play a significant role in the development and progression of PID, highlighting the need for further in‐depth investigation, with PICF offering a practical, noninvasive sampling method.